DirectMX – One-Step Reconstitution of Membrane Proteins From Crude Cell Membranes Into Salipro Nanoparticles - Lloris-Garcerá, Pilar; Klinter, Stefan; Chen, Liuhong; Skynner, Michael J.; Löving, Robin; Frauenfeld, Jens (Frontiers in Bioengineering and Biotechnology, 2020)
Integral membrane proteins (IMPs) are central to many physiological processes and represent ∼60% of current drug targets. An intricate interplay with the lipid molecules in the cell membrane is known to influence the stability, structure and function of IMPs. Detergents are commonly used to solubilize and extract IMPs from cell membranes. However, due to the loss of the lipid environment, IMPs usually tend to be unstable and lose function in the continuous presence of detergent. To overcome this problem, various technologies have been developed, including protein engineering by mutagenesis to improve IMP stability, as well as methods to reconstitute IMPs into detergent-free entities, such as nanodiscs based on apolipoprotein A or its membrane scaffold protein (MSP) derivatives, amphipols, and styrene-maleic acid copolymer-lipid particles (SMALPs). Although significant progress has been made in this field, working with inherently unstable human IMP targets (e.g., GPCRs, ion channels and transporters) remains a challenging task. Here, we present a novel methodology, termed DirectMX (for direct membrane extraction), taking advantage of the saposin-lipoprotein (Salipro) nanoparticle technology to reconstitute fragile IMPs directly from human crude cell membranes. We demonstrate the applicability of the DirectMX methodology by the reconstitution of a human solute carrier transporter and a wild-type GPCR belonging to the human chemokine receptor (CKR) family. We envision that DirectMX bears the potential to enable studies of IMPs that so far remained inaccessible to other solubilization, stabilization or reconstitution methods.